FINANCIAL INNOVATIONS IN PROMOTING DEVELOPMENT OF FINANCIAL MARKET AND NATIONAL ECONOMY - I. Krupka (Вісник Київського національного університету імені Тараса Шевченка. Серія Економіка)
Approaches to the interpretation of financial innovation are considered and systematized. The importance of innovative financial instruments to hedge risks and financial market development in globalization are proved.